Electrodeposition of Co-Ni-Fe on Railway Fastener - M Taib, Y.; Salleh, Z.; R. N. M. Masdek, N.; Jumahat, A.; Kalam, A.; Z. Abu, M. (International Journal of Engineering and Technology, 2018)
Electrodeposition is known as a simple and low-cost method to synthesize good-quality coating with excellent hardness. Co-Ni-Fe is one of the new coating elements and has greater properties in terms of aesthetic and physical properties. The objectives of this project are to carry out electrodeposition of Co-Ni-Fe towards railway clip and to investigate the corrosion formed, thickness of coating layer and hardness of the electrodeposited Cobalt-Nickel-Iron (Co-Ni-Fe) ) alloy coating of the railway clip. The railway clip is made of high carbon steel. The electrodeposition of Co-Ni-Fe on the railway clip plays important role in enhancing the mechanical behaviour of the coating.  Due to its large size, half of the clip was electrodeposited while the other half was left uncoated. The railway clip was electrodeposited at duration of 15 minutes. The pH and working temperature of the sulphate solution were pH 2 and 50℃ with tolerance ± 5℃, respectively. The whole clip was then cut into two halves; the electrodeposited and uncoated. The electrodeposited half was then cut into five pieces. One piece was used for hardness test and the other four pieces were used for corrosion properties. The four pieces were soaked into four types of solution; sulphuric acid (H2SO4), alkali (NaOH),), salt water and distilled water with initial pH 4.8, 11.5, 7.0 and 6.0 respectively. The four pieces were left soaked in the solution for seven days. After seven days, the formation of rust on each piece was observed. FESEM and EDX tests were conducted and two regions of the cross-section of the sample were analysed. The regions analysed had different thickness of coating layer and the average thickness of the coating layer on region 1 and region 2 were 413μm 141.6μm respectivelyIn the hardness test, it was recorded the non-coated fastener had higher average hardness (498.3 Hv) compared to the Co-Ni-Fe coated fastener (339.9 Hv).
Keywords: Coating; Corrosion; Co-Ni-Fe; Electrodeposition; Railway fastener